2009
DOI: 10.1115/1.3109994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wick Characteristics on the Thermal Performance of the Miniature Loop Heat Pipe

Abstract: Two phase heat transfer devices based on the miniature version of loop heat pipe (LHP) can provide very promising cooling solutions for the compact electronic devices due to their high heat flux management capability and long distance heat transfer with minimal temperature losses. This paper discusses the effect of the wick properties on the heat transfer characteristics of the miniature LHP. The miniature model of the LHP with disk-shaped evaporator, 10 mm thick and 30 mm disk diameter, was designed using cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(55 citation statements)
references
References 15 publications
0
53
1
1
Order By: Relevance
“…For ALHPs, most recent studies focus on the performance improvement of the evaporator wick, and quite a few researchers have developed and investigated the biporous or bidisperse wicks to enable the evaporator with high capillary pumping capability, and low flow resistance yet with excellent evaporative heat transfer performance [63][64][65][66][67].…”
Section: Design Optimizationmentioning
confidence: 99%
“…For ALHPs, most recent studies focus on the performance improvement of the evaporator wick, and quite a few researchers have developed and investigated the biporous or bidisperse wicks to enable the evaporator with high capillary pumping capability, and low flow resistance yet with excellent evaporative heat transfer performance [63][64][65][66][67].…”
Section: Design Optimizationmentioning
confidence: 99%
“…Unlike conventional heat pipes in which wick structure is built on the internal wall of the pipe, the thermosiphon internal wall has none wick to be built. As well known, the function of the wick is for capillary of liquid from condenser section to evaporator section in the heat pipe and vaporizing the liquid when heat is applied at the heating area (Zhang et al, 2002 andSingh et al, 2009).…”
Section: Principle Of Operationmentioning
confidence: 99%
“…Experimental results showed that the LHP-acetone start up is faster than the LHPmethanol and its evaporator wall temperature is lower at steady state. Singh et al [18] studied the effect of wick characteristics on the thermal performance of the Miniature Loop Heat Pipe. Different materials and porous structures have been investigated to improve the efficiency of the heat exchange process inside the evaporation zone.…”
Section: Introductionmentioning
confidence: 99%